2008
DOI: 10.1021/ja801883t
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamical Equilibrium of Binary Supramolecular Networks at the Liquid−Solid Interface

Abstract: Coadsorption of two different carboxylic acids, benzenetribenzoic acid and trimesic acid, was studied at the liquid-solid interface in two different solvents (heptanoic and nonanoic acid). Independent alteration of both concentrations in binary solutions resulted in six nondensely packed monolayer phases with different structures and stoichiometries, as revealed by means of scanning tunneling microscopy (STM). All of these structures are stabilized by intermolecular hydrogen bonding between the carboxylic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
205
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(217 citation statements)
references
References 40 publications
11
205
0
1
Order By: Relevance
“…[121][122][123] The need to explore well-ordered patterns at the molecular scale has made Scanning Tunneling Microscopy (STM) [124,125] an extensively employed and extremely powerful tool to study supramolecular materials with a sub-molecular resolution. [126][127][128][129][130] The sub-nanometer resolution that can be reached by STM makes it possible to gain exhaustive information on the interactions between molecule-molecule and moleculegraphene (or graphite) surface. In the last years, the majority of the investigations of the non-covalent functionalization of graphene were focused on well-known organic semiconductors featuring an extended aromaticity, taking advantage of their unique chemical structure promoting π-π interactions with graphene.…”
Section: Non-covalent Functionalization Of Graphene: Towards Structurmentioning
confidence: 99%
“…[121][122][123] The need to explore well-ordered patterns at the molecular scale has made Scanning Tunneling Microscopy (STM) [124,125] an extensively employed and extremely powerful tool to study supramolecular materials with a sub-molecular resolution. [126][127][128][129][130] The sub-nanometer resolution that can be reached by STM makes it possible to gain exhaustive information on the interactions between molecule-molecule and moleculegraphene (or graphite) surface. In the last years, the majority of the investigations of the non-covalent functionalization of graphene were focused on well-known organic semiconductors featuring an extended aromaticity, taking advantage of their unique chemical structure promoting π-π interactions with graphene.…”
Section: Non-covalent Functionalization Of Graphene: Towards Structurmentioning
confidence: 99%
“…Like in UHV, the focus has been on in-plane structures [28][29][30][31][32][33][34][35][36][37][38] with structural motifs based on benzene-1,3-dicarboxylic acid (isophthalic acid, IPA), benzene-1,3,5-tricarboxylic acid (trimesic acid, TMA) and higher homologues being of particular interest due to their ability to form extended networks and/or exhibiting random tilings and analogies to glasses. Studies of layers where molecules adopt an upright orientation and exhibit a dense packing are scarce and only comprise alkoxy substituted aromatic monocarboxylic acids [39][40] as well as IPA and TMA.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] Although in these two works different molecular systems have been chosen to tackle such a complex task, authors showed that the chemical design of molecular building blocks is not the only requirement to fulfill when trying to pre-program self-assembled patterns at the solid-liquid interface. This is true even when only one molecular module is used to generate 2D architectures at surfaces: De Feyter and coworkers [14] highlighted the paramount importance of the concentration in polymorphism control of single-component patterns by using alkoxylated dehydrobenzo annulenes (DBAs).…”
mentioning
confidence: 99%
“…[20] The combination of in-silico modeling with STM experimental data was used recently to unfold a semi-quantitative view of pattern formation in multicomponent systems. [15,21] The recent contribution by Lackinger and coworkers [15] represents a first step in bridging thermodynamic modeling and experiment. Authors focused their endeavor on the formation of multiple phases as a function of concentration in 2D SAMs obtained from the deposition of two components (Fig.…”
mentioning
confidence: 99%